Pengaruh Kecerdasan Emosional Dan Pengalaman Kerja Terhadap Kinerja Karyawan PT Bank Sumut Kantor Pusat Medan - Supriadi Supriadi; Nadia Putri Mulia; Julienda Br Harahap (Jurnal Prodi Fakultas Ekonomi-UISU, 2023)
The formulation of the problem in this research is how influences know of emotional intelligence on employes perfomance. How influence know of work experience on employes perfomance.How influence knowof emotional intelligence and work experience on employes perfomance at PT. Bank Medan Headquarters. The method used in this research is to test the validity, reliability, classical assumption test, linear regression, and hypothesis testing. The data were measured or processed using SPSS, with a samplse used a questionnaire which was distributed to 83 employes at PT. Bank Sumut Medan Headquarters. The results of this research indicate that the emotional intelligence variable has a positive and significant effect on employes perfomance. The work experience variable has a positive significant effect on employes perfomance. The emotional intelligence and work experience variables have a positive and significant effect on employes performance.